The Association Between Hippocampal Volume and Level of Attention in Children and Adolescents - Kim, Tae-Hyeong; Choi, Eunhye; Kim, Hayeon; Kim, Shin-Young; Kim, Yeeun; Kim, Bung-Nyun; Park, Subin; Jung, Kyu-In; Park, Bumhee; Park, Min-Hyeon (Frontiers in Systems Neuroscience, 2021)
The hippocampus, which engages in the process of consolidating long-term memories and learning, shows active development during childhood and adolescence. The hippocampus also functionally influences attention. Based on the influence of hippocampal function on attention, it was expected that the volume of the hippocampus would be associated with the difference in attention during childhood and adolescence, in which the brain actively develops. Thus, this study examined the association between hippocampal volume and attention metrics measured by the continuous performance test (CPT) in 115 children and adolescents (mean age=12.43±3.0, 63 males and 52 females). In association studies with both auditory and visual attention, we found that the bilateral hippocampal volumes showed negative relationships with auditory omission errors. A smaller volume of the left hippocampus also led to a longer auditory response time. However, visual attention did not show any significant relationship with hippocampal volume. These findings were consistent even after adjusting for the effects of related covariates (e.g., age, insomnia and depression). Taken together, the current study suggested that the increase in hippocampal volume during childhood and adolescence was significantly associated with better auditory attention